Development of sodium hybrid quasi-solid electrolytes based on porous NASICON and ionic liquids. Issue 15 (December 2021) - Martínez-Cisneros, C.S.; Pandit, B.; Antonelli, C.; Sanchez, J.Y.; Levenfeld, B.; Varez, A.
Highlights: Novel Na-hybrid electrolytes based on porous NASICON and commercial ionic liquids, has been prepared. These new hybrid electrolytes present an enhanced conductivity (around 1 mS cm-1 at 30°C) of one order of magnitude respect to pore-free sintered NASICON samples Thinner films of this porous NASICON would permit the manufacture of functional macroporous inorganic separators acting as a Na + reservoirs. Abstract: Lithium-ion batteries are currently the alternative of choice to overcome the increasing demand of energy. However, besides the scarcity of lithium and limited geolocation, it is believed that such batteries have already reached their maximum maturity. Sodium batteries emerge as an alternative to produce the new, so called, post-lithium batteries. In this study, we explore (i) the effect of sodium content and sintering temperature in solid electrolytes based in NASICON-type compounds and (ii) the use of two methodologies to obtain porous NASICON samples: application of natural substances and organic materials as pore-formers and freeze casting. The main purpose is the attainment of hybrid quasi-solid state electrolytes, with enhanced room temperature conductivity, based on porous ceramic electrolyte layers infiltrated with ionic liquids. Using this approach, porous samples with different microstructure and porous morphology and distribution were achieved, providing an enhancement in conductivity (ranging from 0.45 to 0.96 mS cm −1 at 30 °C) of one order of magnitude for infiltrated samples respect to pore-free samples. According to these results the porous NASICON might be considered as a functional macroporous inorganic separator that can act as a Na + reservoir.